Developing Leadership for Creative Efforts: A Preface - Michael D. Mumford; Carter Gibson (Advances in Developing Human Resources, 2011)
Michael D. Mumford is the George Lynn Cross distinguished research professor of psychology at the University of Oklahoma where he directs the Center for Applied Social Research. He received his doctoral degree from the University of Georgia in 1983 in the fields of industrial and organizational psychology and psychometrics. He is a fellow of the American Psychological Association (Divisions 3, 5, 10, 14), the Society for Industrial and Organizational Psychology, and the American Psychological Society. He has written more than 270 articles on leadership, creativity, innovation, planning, and ethics. He has served as senior editor of The Leadership Quarterly, and he sits on the editorial boards of the Creativity Research Journal, The Journal of Creative Behavior, IEEE Transactions on Engineering Management, and Ethics and Behavior, among other journals. He has served as principal investor on grants totaling more than US$30 million from the National Science Foundation, The National Institute of Health, the Department of Defense, the Department of Labor, and the Department of State. He is a recipient of the Society for Industrial and Organizational Psychology’s M. Scott Myers Award for Applied Research in the Workplace.
Keywords: leadership; creativity; innovation; development